Hospitality on a Leash: A Study of the Online Visibility, Availability and Distribution of Pet-friendly Accommodations in Romania - Gabriela MUNTEANU (Studia Universitatis Babeş-Bolyai: Geographia, 2025)
Hospitality on a Leash: a Study of the Online Visibility, Availability and Distribution of Pet-Friendly Accommodations in Romania. The present paper explores the growing phenomenon of pet travel within contemporary tourism, focusing on the preferences of dog owners and the operational implications for hospitality and destination management. Drawing on interdisciplinary literature and empirical data from Romania, the paper examines the emotional, logistical, and structural factors shaping pet-inclusive travel, emphasizing both opportunities and challenges. A central theme is the disconnect between increasing demand and the pet-friendly infrastructure in destinations. The study provides an analysis of the spatial distribution of pet-friendly accommodations across Romanian counties using publicly available data from major travel platforms. Uneven patterns are revealed: while urban centers and major tourist destinations dominate in absolute numbers, true inclusivity remains rather localized and fragmented. Four county typologies emerge based on the intersection of total accommodation numbers and promoted pet-friendliness, pointing to both strategic opportunities and infrastructural gaps. Despite Romania’s rising domestic pet travel demand, it still lags behind many EU countries in terms of online-listed pet-friendly options. The paper concludes by advocating for a systemic, ethical approach that balances economic potential with environmental sustainability and animal welfare, framing pet travel as part of broader cultural geographies of mobility, inclusion, and human-animal relations.